Application of an average strain energy density criterion to obtain the mixed mode fracture load of granite rock tested with the cracked asymmetric four-point bend specimens. (October 2018) - Razavi, S.M.J.; Aliha, M.R.M.; Berto, F.
Highlights: Mixed mode I/II fracture of granite rock is studied using Asymmetric Four Point Bend (AFPB) specimen. Fracture loads of the tested rock samples were predicted using Average Strain Energy Density (ASED) criterion. The practical ability of ASED criterion was demonstrated for predicting the mixed mode fracture behavior of rocks. Abstract: Mixed mode brittle fracture behaviour of granite rock is studied experimentally and theoretically using Asymmetric Four Point Bend (AFPB) specimens containing pre-cracks subjected to different mixed mode loading conditions, ranging from pure mode I to pure mode II. The main aim of this paper is twofold. First, to present a complete set of experimental results on fracture of pre-cracked granite samples under various in-plane loading mixities, and second, to predict the fracture loads of the tested rock samples under mixed mode I/II conditions using an energy-based criterion, namely the Average Strain Energy Density (ASED) criterion. Good agreement is found between the experimentally obtained fracture loads and the theoretical predictions based on the constancy of the mean strain energy density over the material volume. It is shown that the ASED criterion is able to provide well predictions for the fracture loads of the investigated rock material containing a pre-crack.